Miracle on 34th Street (1994) [videorecording (DVD)] - Attenborough, Richard; Perkins, Elizabeth, 1960-; McDermott, Dylan; Wilson, Mara (Twentieth Century Fox Home Entertainment, Inc., 2000)
Remake of the 1947 movie in which Kris Kringle (Attenborough), while working at Macy's, encounters an unbelieving child (Wilson) and goes on trial to prove he is Santa.